Enhanced maternal and child health nurse care for women experiencing intimate partner/family violence: protocol for MOVE, a cluster randomised trial of screening and referral in primary health care - Taft Angela J; Small Rhonda; Humphreys Cathy; Hegarty Kelsey; Walter Ruby; Adams Catina; Agius Paul (BMC, 2012)
Abstract Background Intimate partner violence (IPV) can result in significant harm to women and families and is especially prevalent when women are pregnant or recent mothers. Maternal and child health nurses (MCHN) in Victoria, Australia are community-based nurse/midwives who see over 95% of all mothers with newborns. MCHN are in an ideal position to identify and support women experiencing IPV, or refer them to specialist family violence services. Evidence for IPV screening in primary health care is inconclusive to date. The Victorian government recently required nurses to screen all mothers when babies are four weeks old, offering an opportunity to examine the effectiveness of MCHN IPV screening practices. This protocol describes the development and design of MOVE, a study to examine IPV screening effectiveness and the sustainability of screening practice. Methods/design MOVE is a cluster randomised trial of a good practice model of MCHN IPV screening involving eight maternal and child health nurse teams in Melbourne, Victoria. Normalisation Process Theory (NPT) was incorporated into the design, implementation and evaluation of the MOVE trial to enhance and evaluate sustainability. Using NPT, the development stage combined participatory action research with intervention nurse teams and a systematic review of nurse IPV studies to develop an intervention model incorporating consensus guidelines, clinical pathway and strategies for individual nurses, their teams and family violence services. Following twelve months' implementation, primary outcomes assessed include IPV inquiry, IPV disclosure by women and referral using data from MCHN routine data collection and a survey to all women giving birth in the previous eight months. IPV will be measured using the Composite Abuse Scale. Process and impact evaluation data (online surveys and key stakeholders interviews) will highlight NPT concepts to enhance sustainability of IPV identification and referral. Data will be collected again in two years. Discussion MOVE will be the first randomised trial to determine IPV screening effectiveness in a community based nurse setting and the first to examine sustainability of an IPV screening intervention. It will further inform the debate about the effectiveness of IPV screening and describe IPV prevalence in a community based post-partum and early infant population. Trial registration ACTRN12609000424202